The Influence of Social Media, Content Marketing on Purchasing Decisions Through Customer Engagement Online Travel Agent - Nawang Hakim Mega Angkasa; Oni Yudo Sundoro; Yana Tatiana (Dinasti International Journal of Digital Business Management, 2024)
The online travel agent (OTA) business is affected by rapid advances in digital technology. The purpose of this research is to study how content marketing and social media usage influence consumers' decision to make a purchase through their engagement with the Traveloka App. This research utilizes a quantitative method known as Partial Least Square - Structural Equation Modeling (PLS-SEM). Data was collected through questionnaires distributed to 200 people in Jabodetabek who use Traveloka and have purchased tickets within the last six months. The results show that content advertising and social media have a positive and significant influence on customer engagement and purchase decisions; the higher the customer engagement, the more likely they are to buy. This study also found that customer engagement acts as an intervening variable that affects purchase. The findings of this study have significant consequences for digital marketing strategies in the OTA industry, particularly in terms of how businesses can increase customer engagement to encourage them to make better purchasing decisions. The research suggests that to increase customer engagement and improve the quality of content and interactions on social media is crucial. Ultimately, marketing campaigns and product sales through digital platforms will become more effective.